Emergency caesarean section for fetal distress in labour is associated with smaller babies than spontaneous vaginal delivery. (18th April 2012) - Prior, T; Wild, M; Mullins, E; Bennett, P; Kumar, S
Abstract : Birthweight is known to be an important independent prognostic factor for morbidity and mortality of pre-term infants. However, little is known regarding the effect of birthweight on an infants' ability to tolerate labour. We set out to compare birthweights in term infants born by spontaneous vaginal delivery and those born by emergency caesarean section for suspected fetal compromise (fetal distress). One hundred term infants born by emergency caesarean section due to fetal distress in labour and 100 infants born by spontaneous vaginal delivery were identified from hospital birth records. Birthweight and gestation at delivery were documented for all infants and birthweight centiles calculated. Infants born by emergency caesarean section due to an identifiable cause such as umbilical cord prolapse or placental abruption were excluded. Infants delivered by emergency caesarean section for fetal distress had a mean birthweight of 3415g, a median of 3376, and a range of 2144g – 4810g. Infants delivered by spontaneous vaginal delivery had a mean birthweight of 3535g, a median of 3550g, and a range of 2600g – 4480g. When matched for gestation, infants born by emergency caesarean section had a significantly lower mean birthweight centile (46), compared to infants born by spontaneous vaginal delivery (56) (p=0.02). This data suggests that infants born by emergency caesarean section due to fetal distress are less well grown (when matched for gestation) than infants born by spontaneous vaginal delivery, and that feto-placental reserves are related to birthweight even in the apparently appropriately grown fetus.